Strategi Adaptasi Non-struktural dalam Menghadapi Banjir Pasang: Studi Kasus Kota Pekalongan - Ramadhani M. Andrea; Prawata H. Sudharto; Kismartini Kismartini (Seminar Nasional Lahan Suboptimal, 2020)
Andrea RM, Sudharto PH, Kismartini K.  2020. Non-structural adaptation strategies in facing tidal flood: case study of Pekalongan city. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The phenomenon of tidal flooding in the coastal area of Pekalongan City has occurred for more than 10 years. Tidal floods occurred inundating nearly 51% of the total area of Pekalongan City. This situation has resulted in damage to all sectors, such as the physical, social, economic, health, and safety sectors. Adaptation strategies are needed to reduce the risk of loss which is quite high. A non-structural integrated approach can be done by optimizing the capacity of the community in areas prone to tidal flooding. Writing this manuscript aims to find an adaptation strategy in dealing with the tidal flood phenomenon, which is taken from the case study of Pekalongan City. The literature study technique is used to obtain a good adaptation strategy to prepare the disaster-resilient city of Pekalongan. The results of the literature study explain that the non-structural adaptation strategy that has been carried out by the Pekalongan City government is by optimizing actions that focus on increasing community preparedness. This increase is carried out through outreach/ outreach efforts, the formation of community organizations, and an integrated early warning mechanism.